2019
DOI: 10.1016/j.physe.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow lattice thermal conductivity and electronic properties of monolayer 1T phase semimetal SiTe2 and SnTe2

Abstract: 2H phase (trigonal prismatic D3h) of layered two-dimensional (2D) transition metal dichalcogenides (TMDs) have attracted a lot of interests due to the superior electronic and optoelectronic properties. However, flexible electronic devices and thermoelectric performances based on 2H phase have been potentially limited by the strain sensitive electronic band gap and high lattice thermal conductivity ( ). Here, we predict and calculate two 1T (octahedral Oh) phase monolayer telluride materials SnTe2 and SiTe2 wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 63 publications
4
18
0
Order By: Relevance
“…Silicene and germanene are the representatives of hexagonal lattice and SiTe 2 belongs to TMDs 27 and is regarded as a superior thermoelectric material. 25,28 Based on Table 1, we can find that κ is proportional to the ω a D , verifying the correctness of the Slack model prediction in 2D materials qualitatively.…”
Section: Resultssupporting
confidence: 68%
“…Silicene and germanene are the representatives of hexagonal lattice and SiTe 2 belongs to TMDs 27 and is regarded as a superior thermoelectric material. 25,28 Based on Table 1, we can find that κ is proportional to the ω a D , verifying the correctness of the Slack model prediction in 2D materials qualitatively.…”
Section: Resultssupporting
confidence: 68%
“…In the top 50 listed here we have excluded any predictions for which we could find thermoelectric reports outside our corpus. *Materials reported as good thermoelectrics while this manuscript was being prepared and reviewed [36][37][38] .…”
Section: Methodsmentioning
confidence: 99%
“… 24 The other Si x –Te y compound is silicon ditelluride (SiTe 2 ), 31 34 whose electrical, thermal, and magnetic properties have recently drawn a number of investigations. 35 37 The crystal structure of SiTe 2 is identified to be the CdI 2 -type 34 , 38 as other 2D IV–VI 2 materials, although it was suggested that it might also exist in the Si 2 Te 3 structure with Si deficiency. 39 …”
Section: Introductionmentioning
confidence: 99%